PENGARUH STORY TELLING TERHADAP PENGETAHUAN POLA KONSUMSI SAYUR DAN BUAH PADA ANAK USIA 4-6 TAHUN DI RT 015 DESA SULI KECAMATAN SALAHUTU - Abdul Thalib; Indah Huka; Yona Latuperisa; Kreshas J.A Noija (STIKES Pasapua Ambon, 2021)
Introduction: Storytelling can be given knowledge to children who previously did not like vegetables with media stories that children will be interested in. Therefore an appropriate method is needed in conveying nutrition education, especially regarding fruits and vegetables to children, nutrition education using the storytelling method. The purpose of this study was to analyze the effect of storytelling on knowledge of fruit and vegetable consumption patterns in children aged 4-6 years in RT 015 Suli Village, Salahutu District. By having 32 Respondents. Method: The method used in this research is a pre-experimental design with one group pretest-posttest. The research data was obtained by providing a knowledge questionnaire on consumption patterns of vegetables and fruit. This data analysis uses the Wilcoxon Test. Results: there is an effect of knowledge before and after storytelling on knowledge of consumption patterns of vegetables and fruit in children aged 4-6 years in RT 015 Suli Village, Salahutu District (p=0,000). Conclusion: There is an influence on knowledge of fruit and vegetable consumption patterns in children aged 4-6 years in RT 015 Suli Village, Salahutu District.